The Effect of Tongka Langit Banana Juice on Morphological Abnormalities Spermatozoa in Mice (Mus musculus) Infected by Plasmodium berghei - Hitalesiakwane, Yesty E.; Kaihena, Martha; Samson, Efraim (Jurnal Biologi Tropis, 2025)
Malaria infection by Plasmodium is known to affect human reproduction. One of the reproductive organs affected by malaria infection is the testes. If there is a disorder in the testes, it will affect the spermatogenesis process, so that it can cause morphological abnormalities of the resulting spermatozoa. This study aims to determine the effect of administering Tongka Langit banana juice (Musa troglodytarum) on morphological abnormalities of spermatozoa in mice (Mus musculus) infected with Plasmodium berghei. The results of this study indicate that administering Tongka Langit banana juice can reduce spermatozoa abnormalities. Compared with the dose groups of 0.55g/mice/day and 0.65g/mice/day, administering Tongka Langit banana juice at a dose of 0.75g/mice/day is the most effective dose on reducing the average spermatozoa abnormalities in mice. The carotenoid content in Tongka Langit bananas is thought to ward off Plasmodium berghei infection, the cause of spermatozoa abnormalities in mice.